"The problem with running" - Comparing the propulsion strategy of children with Developmental Coordination Disorder and typically developing children - Diamond, N.; Downs, Jennepher; Morris, Susan (Elsevier, 2014)
Children with Developmental Coordination Disorder (DCD) often have difficulties running. This study compared strategies of propulsion and power generation at the ankle during late stance/early swing in both walking and running in children with and without DCD. Eleven children (six male) aged nine to 12years with DCD were matched by sex and age with 11 typically developing (TD) children. Gait kinematics and kinetics were measured during 4 gait types; normal walking, fast walking, jogging and sprinting using three-dimensional motion analysis. Propulsion strategy during gait was calculated as ankle power divided by the sum of ankle and hip power (A2/A2 + H3). The children with DCD ran slower than the TD children (mean difference [MD] when jogging 0.3 m/s and sprinting 0.8 m/s). Adjusting for speed, those with DCD had smaller propulsion strategy values during jogging (p = 0.001) and sprinting (p = 0.012), explained by reduced ankle power generation at push off (A2) (jogging, MD 2.5 W/kg, p < 0.001) and greater hip flexor power generation at pull off (H3) (jogging, MD 0.75 W/kg, p = 0.013). Similar findings were observed during sprinting. Children with DCD ran with a slow and less efficient running style compared with TD children. Physiotherapy targeting running-specific needs in relation to ankle muscle strength and coordination could enable more participation in running activities.